2019
DOI: 10.1002/nbm.4052
|View full text |Cite
|
Sign up to set email alerts
|

Pulse sequence considerations for quantification of pyruvate‐to‐lactate conversion kPL in hyperpolarized 13C imaging

Abstract: Hyperpolarized 13C MRI takes advantage of the unprecedented 50 000‐fold signal‐to‐noise ratio enhancement to interrogate cancer metabolism in patients and animals. It can measure the pyruvate‐to‐lactate conversion rate, kPL, a metabolic biomarker of cancer aggressiveness and progression. Therefore, it is crucial to evaluate kPL reliably. In this study, three sequence components and parameters that modulate kPL estimation were identified and investigated in model simulations and through in vivo animal studies u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The results from this work support the use of hyperpolarized 13 C MR for in vivo, non‐invasive monitoring of the metabolic effects of inhibition of LDH, and more widely in studies relating to modifications to the Warburg effect. The biomarker of metabolism took the form of the lactate‐to‐pyruvate ratio, which provides a surrogate measure relating to cancer aggressiveness and progression, 26,27 and showed a significant reduction in cases of LDH inhibition by the drug GNE140 but remained relatively consistent in the EGFR‐driven lung cancer model following genetic ablation of LDH‐A . Use of hyperpolarized 13 C MR and the lactate‐to‐pyruvate ratio in oncological studies allows interrogation of the metabolic pathways associated with the Warburg effect and aerobic glycolysis that are prominent in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this work support the use of hyperpolarized 13 C MR for in vivo, non‐invasive monitoring of the metabolic effects of inhibition of LDH, and more widely in studies relating to modifications to the Warburg effect. The biomarker of metabolism took the form of the lactate‐to‐pyruvate ratio, which provides a surrogate measure relating to cancer aggressiveness and progression, 26,27 and showed a significant reduction in cases of LDH inhibition by the drug GNE140 but remained relatively consistent in the EGFR‐driven lung cancer model following genetic ablation of LDH‐A . Use of hyperpolarized 13 C MR and the lactate‐to‐pyruvate ratio in oncological studies allows interrogation of the metabolic pathways associated with the Warburg effect and aerobic glycolysis that are prominent in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides being sensitive to off‐resonance, the used SPSP pulse was also rather long. A long echo time leads to loss of SNR, but a recent study by Chen et al also found that a long echo time for hyperpolarized experiments can cause errors in the estimated kinetics because of the shorter T2* of lactate compared to pyruvate. Therefore, future improvements should include a better SPSP design and/or IDEAL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of individual pulse sequence components and parameters on the quantification of results as imaging biomarkers, e.g. pyruvate-to-lactate conversion rates k pl , has been discussed recently [391]: A profound effect of sequence parameters on k pl was found for the cases of magnetization spoiling by RF pulses, flow suppression by crusher gradients, and intrinsic image weightings due to relaxation. Given the large variety of pulse sequence components used in hyperpolarized MRI, a major challenge for this field will be the standardization of acquisition protocols and data analysis procedures for comparison of results across different sites which, is especially important for the validation of biomarkers in clinical studies.…”
Section: Discussionmentioning
confidence: 99%